Análisis De Muestras Colectadas De Propoleo Proveniente De Apicultores Colombianos (2024)
Propolis, a resin produced by bees from various plant sources, has a wide spectrum of biological properties that position it as a product of great interest in the pharmaceutical, cosmetic and food industries. In Colombia, beekeeping is an activity with great potential, however, the characterization and valorization of propolis are still areas that require further research. This work aims to initiate the characterization of Colombian propolis. The analysis of 22 samples of propolis from 9 departments will be carried out in order to identify its main components, whether or not they depend on the biodiversity of our country and establish the bases for future research for use in veterinary medicine.